Noise Pollution at Work Place and Health Implications - Kitcher, E.D. (My University, 2013)
The aim of this paper is to discuss the prevalence of health implications of noise pollution at work place and to outline preventive measures. An available publication in the sub region of West Africa on the commonest health problem of noise pollution at work place which is noise induced hearing loss was accessed through Pub med and other literature search. Selection of studies which were comparative studies of noise exposed workers and controls were selected. This search provided the needed information on prevalence of occupational hearing loss of workmen. Information on the use of hearing protective devices by the workers was obtained. Preventive measures for occupational hearing loss was outlined Available literature has confirmed significant occupational hearing loss due to exposure of workers to noise pollution. Most of the workers did not use hearing protection devices. The prevalence of occupational hearing loss ranged between 20-56%. Regulation of work environment by governmental control will go a long way to reduce the prevalence of NIHL.